An Ability of Mathematical Representation And Independence of Student Learning in Reciprocal Teaching With Resitation and Self Assesement - Rizai, Muhammad Muhsin; Kartono, Kartono; Rochmad, Rochmad (Universitas Negeri Semarang, 2018)
This study aims to: (1) find out the quality of reciprocal teaching with recitation and self assessment on the achievement of mathematical representation abilities, (2) describe the ability of mathematical representation in terms of student learning independence, and (3) determine the effect of learning independence on students' mathematical representation abilities in reciprocal teaching with recitation and self assessment. This research is a mixed method type of concurrent embedded design type. The subject of this study was determined based on the learning independence score using a learning independence questionnaire in the eighth grade students of MTs Urwatil Wutsqo Jepara. Data collection techniques are using tests, questionnaires, and interviews. The quality of learning is analyzed based on three quality categories, namely planning, implementation and assessment. The effect of learning independence on mathematical representation ability was analyzed based on simple linear regression test. The results showed that (1) the three domain qualities of learning were categorized as good, so it was concluded that the quality of reciprocal teaching with recitation and self-assessment of mathematical representation abilities was good. (2) students with high learning independence are able to master all mathematical representation indicators well compared to students with moderate and low learning independence; (3) learning independence has a positive effect on the ability of mathematical representation on reciprocal teaching with recitation and self assessment.